(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Sugar Goods Express is a proposed sugar retailing business for dyed common sugar. A survey method was used in determining the acceptability of the proposed business considering the product, price, place and promotion. Using this method, the researchers prepared a structured questionnaire and administered them to one hundred (100) respondents in Punturin, Valenzuela City where the proposed business will be located and Novaliches, Quezon City where the researchers study. Majority of the respondents who participated in the survey are female and employees. The result of the survey reveal that among the choices on the types of sugar, washed is the most frequently consumed. The price acceptability was presented based on the weekly consumption. In terms of proposed location, 74% considered that it is accessible. Product discount and freebies topped the list of proposed promotional tools at 53% and 24%, respectively. This research is focused on the production of Sugar Goods Express in Punturin, Valenzuela City. This provides introduction for a retailing sugar industry with a new concept, introducing colorful and flavored sugar. Based on the results of the survey that focused on the acceptability of 4Ps, the proposed business is feasible and has the potential to compete in the market. Since the proposed product is consumed by every household, the researchers are confident that once established, Sugar Goods Express will make its name in the retailing industry.